One crazy summer - Williams-García, Rita (New York : SCHOLASTIC INC., 2012)
Set during one the most tumultuous years in recent American history, one crazy summer is the heartbreaking, funny tale of three girls who travel to Oakland, California, in 1968 in search of the mother who abandoned them. It's an unforgettable story told by a distinguished author of books for children and teens, Rita Williams-Garcia.
Ubicada durante uno de los años más tumultuosos de la historia reciente de los Estados Unidos, un verano loco es el desgarrador y divertido relato de tres chicas que viajan a Oakland, California, en 1968 en busca de la madre que las abandonó. Es una historia inolvidable contada por una distinguida autora de libros para niños y adolescentes, Rita Williams-Garcia.
Keywords: NORTH AMERICAN LITERATURE -- NOVEL; LITERATURA NORTEAMERICANA -- NOVELA